Review: Research and application of bamboo and jute fibers reinforced polymer composite in Vietnam - Dieu, Tran Vinh; Chuong, Bui; Tung, Nguyen Huy; Minh Ngoc, Phan Thi; Duy Linh, Nguyen Pham; Huan, Pham Gia; Thuy, Nguyen Thi; Dung, Tran Kim; Ninh, Tran Hai (Vietnam Journal of Chemistry, 2014)
In Vietnam, 102 species with 19 geniuses of bamboo families are recorded. But the most popular is Dendrocalamus membranaceus Munro. It has been selected forestation in the provinces from the North Central to Central area of Vietnam. Fabricated bamboo fibers by mechanical and steam exploded techniques consist of short and long fibers. Different methods of bamboo fiber surface treatment have been carried out and alkaline treatment was the best method. Thermoplastic resin (polypropylene -PP) and thermoset resin (unsaturated polyester - UP and epoxy - EP) were used as matrices of composites. Maleic anhydride grafted polypropylene (MAPP) was chosen as coupling agent to improve adhesion between PP and bamboo fiber. Polymer composite materials were reinforced by only bamboo fiber according to skin-core and ply-by-ply structure. Bamboo-PP resin composites with 50 wt. % of bamboo fiber has higher mechanical properties in comparison with pure PP. Bamboo- UP resin composites possess good mechanical and chemical properties, whereas bamboo-EP resin composites show unsatisfied water and chemical resistance. Skin-core structure hybridization of jute with glass fiber in skin increased impact strength significantly (1.8-2.0 times). This hybrid composite was used for making chair, tables, boats, construction panels, etc… Short bamboo fiber-PP composites are going to prepare pall rings using for waste water treatment in the present of micro-organism.